(untitled) (Psicologia USP, 2011)
With the intention of presenting the evasive matter which is the hysteria, I decided to overlook it using the theories and works of Freud, assuming the period between 1886 and 1898. The hysteria, since always an heterogeneous object of multiple belongings, claimed by the natural and the supernatural, by reason and superstition, demanded an inquiry if, so often closed either in the body or in the spirit, would be whether or not a disease. We are interested in the hysteria from the treatment given by Freud. As to the reading keys that guided this research I anticipate some to the guidance of the reader: the very historical and chronological presentation of the theme and the works of Freud about it. Conceptually, the relationship between mind and body, the thesis of ideogenia in the etiology of hysteria, the gradual introduction of infantile sexuality and finally, the overcoming of the traumatic hypothesis, supported by the seduction theory, towards the admission of fantasy. All this, in order to practice an understanding on the Freudian theory which recognizes the specificity of his production from an alternative route, which does not take into account the fact of neither a rupture nor a conceptual continuity in its elaboration.